Iot Based Plants Disease Detection Using Convolution Neural Network (CNN) and Support Vector Machines (SVM) - M.Saravanan, M.Ramkumar*, M.Sharon Nisha, Rajesh.N, M.P. Thiruvenkatasuresh (International Journal of Advanced Science and Technology, 2020)
Every country’s economic is extremely reliant on agricultural efficiency. Thus in the field of farming, increasing the yield is very important and for increasing the yield, the detection of disease in the early stage in plant is essential. In order to identify a plant disease the utilization of an automated disease detection strategy is helpful in protecting the plants and in increasing the yield. In this paper we proposed a method for detecting the disease in banana leaves using IoT devices with the help of convolution neural network and support vector machine and we suggested a method for automation by robotics in forming. In the proposed work an algorithm for picture segmentation is developed for detection of leaf diseases in banana tree. Also, the convolution neural network is utilized to determine the kinds of disease. From the experimental results it is absorbed that our proposed method gives more accurate result than the existing methods